Building relationships and capacity with First Nation communities affected by mine closure - Slater, W.; Moar, R.; Lemieux-Tremblay, J. (Mine Closure 2011: Proceedings of the Sixth International Conference on Mine Closure, 2011)
Past mining projects in northern Canada have often adversely affected local First Nation communities and people. Promises of employment and economic benefits have sometimes not materialised. Environmental changes have affected people’s subsistence and traditional activities. Lack of trust and ineffective communications led to perceptions about effects and associated changes in subsistence and traditional use patterns. Given past experiences, First Nation governments and citizens are often skeptical about whether mine closure and remediation projects will deliver positive results for their communities. Mine closure and remediation at abandoned mines offers an opportunity to not only reclaim the environment, but also to rebuild relationships with local First Nations and provide long-term social and economic benefits. The Canadian Government is funding several mine closure projects in Yukon, Canada and is working with a number of First Nation governments as well as the Government of Yukon in planning for these projects. This paper explores the administrative planning structures and processes established among Canada, Yukon and First Nation governments for two of these government-sponsored abandoned mine closure projects. All three levels of government hope that these processes will facilitate effective involvement and participation of First Nations in the planning phase of the mine closure. The First Nation of Nacho Nyak Dun based in Mayo, Yukon is involved in closure planning for the United Keno Hill Mines property. The Little Salmon Carmacks First Nation based in Carmacks, Yukon is involved in closure planning for the Mt. Nansen Mine. Governance structures for closure planning at these two mines are substantially different, but both First Nations have similar overall objectives for the closure projects. Both First Nations face capacity challenges that can limit their abilities to participate effectively. The paper discusses the strategies utilised by both First Nations and how they have performed. Both First Nations recognise that further work will be required to guide other phases of the closure continuum including implementation and post-closure.